Multidisciplinary approach in the rehabilitation of partial edentulousness: Adjunctive orthodontic and subsequent prosthodontic treatment - Šećerbegović-Srna Irma; Biočanin Vladimir (Serbian Medical Society - Dental Section, Belgrade, 2022)
Introduction Malocclusions in partially edentulous patients represent a special rehabilitation challenge in dentistry. In patients who, in addition to orthodontic problem, also have a certain number of missing teeth, it is necessary to approach in a multidisciplinary manner. This approach implies a synergy of conservative, orthodontic and prosthetic treatment. The aim of this paper was to present a patient with partial edentulism including upper left canine palatally located that was successfully rehabilitated with orthodontic and subsequent fixed prosthodontic treatment. Case report The clinical examination of the 24-year-old patient was followed by additional orthodontic analysis that included analysis of study models, X-rays, and photographs. The patient was found to have ectopic teeth 13 and 23, reverse overbite of the tooth 12, and tooth 26 was extracted in childhood. Due to the prevalence of carious lesions and tooth destruction, the attending dentist planned extraction of teeth 16, 14, 24, 25. It was decided to conduct adjunctive orthodontic treatment in order to achieve tooth levelling and move teeth to the positions planned in the previous analysis. After completion of orthodontic treatment, fixed prosthodontic work was done to achieve complete functional and aesthetic rehabilitation.